A novel strategy for identifying hepatotoxic constituents in traditional Chinese medicine using dose-normalized intracellular accumulation as a cytotoxicity indicator: a case study of Jinlingzi San - Gu, Xiaoting; Wang, Hanyang; Li, Keran; Wu, Cuiting; Di, Xin (Frontiers in Pharmacology, 2025)
IntroductionHerb-induced liver injury associated with traditional Chinese medicine (TCM) has increasingly attracted scientific attention. However, the rapid and effective methods for elucidating the material basis of hepatotoxicity in TCM are still lacking. This study developed a strategy based on the use of dose-normalized intracellular accumulation as a cytotoxicity indicator to identify key hepatotoxic components in TCM.MethodsJinlingzi San (JLZS) composed of Fructus Toosendan (FT) and Rhizoma Corydalis (RC) was used as a model sample in this study. Hepatotoxicity was evaluated through both in vivo (14-day continuous gavage administration in rats) and in vitro (24-hour co-incubation with L-02 cells) models. Chemical components in JLZS extract and those accumulated in L-02 cells were identified using LC-MS/MS. The intracellular accumulations of multiple components after exposing L-02 cells to the extracts of JLZS, FT and RC were determined.ResultsJLZS administration resulted in subacute liver injury in rats and demonstrated cytotoxicity to L-02 cells. Seven analytes (coptisine, tetrahydrocoptisine, berberine, jatrorrhizine, palmatine, dehydrocorydaline and toosendanin) were identified in cell lysates following incubation with JLZS. Coptisine and berberine were regarded as the main potential hepatotoxic components in JLZS for its highest dose-normalized intracellular accumulation and the strongest cytotoxicity. In addition, the intracellular accumulations of coptisine and berberine were lower in the JLZS group compared to the RC group alone.DiscussionThe findings suggest that dose-normalized intracellular accumulation serves as a reliable indicator for identifying hepatotoxic constituents in TCM. The observed reduction in intracellular accumulation of coptisine and berberine in the JLZS formulation compared to RC alone maybe reflect the scientific meaning of detoxicity by compatibility with FT and RC.